PJMHS 2022
DOI: 10.53350/pjmhs22165887
|View full text |Cite
|
Sign up to set email alerts
|

Post-traumatic Stress, Work Performance and Employee Satisfaction Among Health Care Workers during the COVID-19 Pandemic

Abstract: Aim: This cross-sectional study was carried out to investigate post-traumatic stress, work performance and employee satisfaction of healthcare workers (HCWs) (nurses and physicians) during the COVID-19 pandemic. Methods: A face-to-face questionnaire was administered to 169 HCWs working in inpatient clinics of two public hospitals in İstanbul, Türkiye. The questionnaire comprised four parts, including a socio-demographic form, the Impact of Event Scale-Revised (IES-R), the Employee Performance Scale and the Em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…Analogically speaking, the unfavourable impact of the aforesaid symptoms also relates to the productivity of an employee, which in turn relates to the organizational performance. The research carried out during the course of the pandemic on a group of 169 employees revealed a weak, yet significant dependency between the general indicator of PTSD and the measurements of PTSD and the efficiency of an employee (Yilmaz, Karakuş, 2022). The symptoms of post-traumatic stress may disrupt verbal memory (Johnsen, Asbjørnsen, 2008; Johnsen, Kanagaratnam, Asbjørnsen, 2008), which may have an impact on the process of learning and weaken the quality of the tasks carried out in particular where people work on worded material.…”
Section: Discussionmentioning
confidence: 99%
“…Analogically speaking, the unfavourable impact of the aforesaid symptoms also relates to the productivity of an employee, which in turn relates to the organizational performance. The research carried out during the course of the pandemic on a group of 169 employees revealed a weak, yet significant dependency between the general indicator of PTSD and the measurements of PTSD and the efficiency of an employee (Yilmaz, Karakuş, 2022). The symptoms of post-traumatic stress may disrupt verbal memory (Johnsen, Asbjørnsen, 2008; Johnsen, Kanagaratnam, Asbjørnsen, 2008), which may have an impact on the process of learning and weaken the quality of the tasks carried out in particular where people work on worded material.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the negative impact of the discussed symptoms also applies to employee productivity, which translates further into organizational performance. A study conducted during the pandemic in a group of 169 employees revealed a weak but significant relationship between the overall PTSD index and PTSD dimensions and employee performance (Yilmaz & Karakuş, 2022). Post-traumatic stress symptoms may impair verbal memory Johnsen, Kanagaratnam, & Asbjørnsen, 2008), which may affect the learning process and impair the quality of tasks performed, especially where verbal material is used.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the negative impact of the discussed symptoms also applies to employee productivity, which translates further into organizational performance. A study conducted during the pandemic in a group of 169 employees revealed a weak but significant relationship between the overall PTSD index and PTSD dimensions and employee performance (Yilmaz & Karakuş, 2022). Post-traumatic stress symptoms may impair verbal memory (Johnsen, Asbjørnsen, 2008; Johnsen, Kanagaratnam, & Asbjørnsen, 2008), which may affect the learning process and impair the quality of tasks performed, especially where verbal material is used.…”
Section: Discussionmentioning
confidence: 99%